Effectiveness of student teams: The role of team personality diversity - Mineiro, R.; Silva, M. G.; Nunes, A. C. (Proceedings of the 20th European Conference on Management Leadership and Governance, ECMLG 2024, 2024)
In current educational landscapes, group work has emerged as a cornerstone of pedagogical strategies, offering students opportunities to cultivate essential skills for future professional endeavors. Central to the success of collaborative efforts lies the intricate interplay of team dynamics, with team personality diversity emerging as a significant factor influencing team effectiveness. Building upon existing research highlighting the critical role of team personality in driving team effectiveness (Kozlowski and Bell, 2003), this study delves into the nuanced relationship between team personality diversity, team processes and emergent states, and collaborative outcomes within student teams. Acknowledging the multifaceted nature of team dynamics, this research adopts a comprehensive approach, drawing upon established theoretical frameworks, such as the input-process-output model (Hackman, 1987; Ilgen et al, 2005), to elucidate the mechanisms through which team personality diversity influences team effectiveness. Through a thoroughly designed two wave methodology and a group-level analytical approach, data were collected from 57 student teams enrolled in undergraduate and graduate courses across diverse academic disciplines during semester 2 of 2022/2023. Our findings reveal that emotional stability diversity within teams exerts a significant yet indirect influence on team satisfaction through its impact on communication openness. Specifically, greater emotional stability diversity leads to diminished communication openness, subsequently leading to reduced levels of team satisfaction. This intricate chain of effects underscores the importance of managing team personality diversity to foster open communication and ultimately enhance satisfaction among team members. While our results align with established theoretical underpinnings, they also prompt critical reflections on team interdependence and the duration of collaborative engagements within academic settings. Consequently, we advocate for further exploration into the potential of team personality diversity within student teams, with an emphasis on longitudinal studies to capture the temporal dynamics of collaborative interactions. This study contributes to the growing body of literature on team dynamics in educational settings, offering valuable insights for educators and practitioners seeking to optimize student experiences, enhance group learning outcomes, and prepare students for their future careers.